Penerapan Intervensi Orientasi Realita terhadap Isi Pikir pada Waham Kebesaran : Literature Review - Magfirohtul Munawaroh; Endah Sari Purbaningsih; Erida Fadila (STIKES Columbia Asia Medan, 2026)
Thought content distortion in schizophrenic patients with grandiose delusions is a major challenge in clinical psychiatric nursing care. This study aims to identify the effectiveness of applying reality orientation interventions (including Cognitive Behavioral Therapy for Psychosis and Metacognitive Training) in improving the thought content of patients with grandiose delusions. Through a systematic literature review method based on the PRISMA guidelines, 10 selected international articles published between 2021 and 2026 were analyzed narratively. The review results indicate that reality orientation interventions are proven effective in reducing delusional beliefs and improving cognitive insight, not by directly confronting delusional conclusions, but by modifying how patients process sensory data and test reality within their environment. These findings are relevant for the development of psychiatric nursing care standards focused on thought content improvement, aiming to accelerate patient recovery in integrated mental health care facilities. The implementation of structured and sustained interventions is expected to improve thought content, enhance adaptive functioning, and support the patient recovery process in integrated mental health care facilities.